Suicidal ideation and reported suicide attempts in Greece during the economic crisis - Economou, Marina (Blackwell Publishing Ltd, 2013)
The financial crisis in Greece is largely impinging on the health and mental health of the population, raising concerns about a potential rise in suicide rates. The aim of this study was to explore changes in suicidal ideation and reported suicide attempts between 2009 and 2011 in a representative sample of the population and in several population subgroups. The socio-economic predictors of suicidal ideation and suicide attempts in 2011 were also investigated. Two nationwide cross-sectional telephone surveys were conducted in 2009 and 2011 using the same methodology. A random and representative sample of 2192 and 2256 people, respectively, took part in the surveys. Between 2009 and 2011, there was a substantial increase in the prevalence of suicidal ideation and reported suicide attempts. People suffering from depression, men, married individuals, people experiencing financial strain, people with low interpersonal trust, and individuals with a history of suicide attempts were particularly vulnerable.